2017
DOI: 10.1186/s13075-017-1467-x
|View full text |Cite
|
Sign up to set email alerts
|

New clues to the nature of immunoglobulin G4-related disease: a retrospective Japanese multicenter study of baseline clinical features of 334 cases

Abstract: BackgroundThe aim was to further characterize immunoglobulin G4-related disease (IgG4-RD) by a large-scale multicenter study of its clinical and laboratory features conducted by multidisciplinary physicians of IgG4-RD in Japan.MethodsVarious specialists retrospectively evaluated IgG4-RD patients diagnosed between 1996 and 2015 in five hospitals by analyzing their baseline clinical features, laboratory, imaging, and pathological test findings, and treatment.ResultsOf the 334 patients listed, 205 were male and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
99
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(115 citation statements)
references
References 37 publications
7
99
1
8
Order By: Relevance
“…Wallace et al [27] identified four distinctive IgG4-RD phenotypes according to organ involvement using latent class analysis. Regarding the heterogeneity in serology, one of the major characteristics of IgG4-RD is elevation of serum IgG4, and studies have generally attached crucial importance to serum IgG4 concentrations, which is also used to assess disease activity [4,5,[28][29][30]. However, serum elevation of IgG4 is the lack of specificity, and normal serum IgG4 concentrations are described even in the setting of active, biopsy-proven disease [3,31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wallace et al [27] identified four distinctive IgG4-RD phenotypes according to organ involvement using latent class analysis. Regarding the heterogeneity in serology, one of the major characteristics of IgG4-RD is elevation of serum IgG4, and studies have generally attached crucial importance to serum IgG4 concentrations, which is also used to assess disease activity [4,5,[28][29][30]. However, serum elevation of IgG4 is the lack of specificity, and normal serum IgG4 concentrations are described even in the setting of active, biopsy-proven disease [3,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…However, serum elevation of IgG4 is the lack of specificity, and normal serum IgG4 concentrations are described even in the setting of active, biopsy-proven disease [3,31,32]. Furthermore, a high percentage of eosinophil; high levels of IgG, IgE, ESR, and CRP; and hypocomplementemia have been frequently reported in IgG4-RD and have been related to outcomes [15,18,29,33], but without excellent specificity. Herein, we proposed clinical patterns in IgG4-RD using cluster analysis based on various baseline blood tests.…”
Section: Discussionmentioning
confidence: 99%
“…Although the frequency of intrathoracic lesions in IgG4- RD has not yet been accurately determined, an assessment of 125 patients with IgG4-RD found lung involvement in 22 (17.6%) [7]. Similarly, lung involvement was reported in 78 (23.4%) of 334 patients with IgG4-RD [8]. Because lung involvement in these studies was defined as clinically or radiographically detectable manifestations in the bilateral pulmonary area, the rate of lung involvement may be higher when mediastinal/bronchial manifestations are included (see Image findings).…”
Section: Clinical Features Of Igg4-rrdmentioning
confidence: 99%
“…Patients with IgG4-RD have been reported to be at high risk of malignancy, especially within one year after onset, suggesting that IgG4-RD is a para-neoplastic syndrome [42]. An analysis of 334 patients found 67 malignancies in 57 patients, with lung cancer being the most frequent, being present in 12 patients [8]. Additionally, an analysis of 294 patients with non-small cell lung cancer who underwent surgical resection found >20 IgG4þ plasma cells per high power field in 35 patients, with six of these 35 patients having an IgG4/IgG ratio >40% [43].…”
Section: Lung Cancermentioning
confidence: 99%
“…Both studies included patients primarily diagnosed with IgG4-related disease in non-vascular organs. More recently, Yamada et al reported that among 334 patients diagnosed with IgG4-related disease on the basis of either by Comprehensive Diagnostic Criteria (CDC) or organ-specific diagnostic criteria, 83 (25%) were found to have lesions in the retroperitoneum or periaorta [40].…”
Section: Involvement Of Other Organs and Isolated Casesmentioning
confidence: 99%